Effect of inhalation on oropharynx collapse via flow visualisation. (30th March 2021) - Bafkar, Omid; Rosengarten, Gary; Patel, Milan.J.; Lester, Daniel; Calmet, Hadrien; Nguyen, Vu; Gulizia, Stefan; Cole, Ivan.S.
Abstract: Computational fluid dynamics (CFD) modelling has made significant contributions to the analysis and treatment of obstructive sleep apnoea (OSA). While several investigations have considered the flow field within the airway and its effect on airway collapse, the effect of breathing on the pharynx region is still poorly understood. We address this gap via a combined experimental and numerical study of the flow field within the pharynx and its impacts upon airway collapse. Two 3D experimental models of the upper airway were constructed based upon computerised tomography scans of a specific patient diagnosed with severe OSA; (i) a transparent, rigid model for flow visualisation, and (ii) a semi-flexible model for understanding the effect of flow on pharynx collapse. Validated simulation results for this geometry indicate that during inhalation, negative pressure (with respect to atmospheric pressure) caused by vortices drives significant narrowing of the pharynx. This narrowing is strongly dependent upon whether inhalation occurs through the nostrils. Thus, the methodology presented here can be used to improve OSA treatment by improving the design methodology for personalised, mandibular advancement splints (MAS) that minimise OSA during sleep.